(untitled) - Conklin, Alfred Russel (Hoboken, N.J., 2007)
This global overview of agriculture discusses all of the primary aspects of food production and relates that information to human nutritional needs. It covers everything from food crop production to food preparation. Beginning with a detailed description of representative farms in different climates, World Food: Production and Use.
Keywords: Food supply,Agriculture,Nutrition,Cung cấp thực phẩm,Nông nghiệp,Dinh dưỡng; Textbooks,Textbooks,Textbooks,Sách giáo khoa,Sách giáo khoa